ANALISIS PERKEMBANGAN USAHA MIKRO DAN KECIL SETELAH MEMPEROLEH PEMBIAYAAN MUDHARABAH DARI BMT AMANAH KECAMATAN MEDAN MARELAN - Ardhansyah Putra Hrp (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2019)
Micro and Small Enterprises (MSEs) are the biggest players in the economic sector that engages in trading and services. In general, the problems faced by MSEs in Medan Marelan, in which micro entrepreneurs of small businesses do not have enough capital to do business. The purpose of this study is to analyze the differences and the development of MSEs between before and after obtaining financing from BMT Amanah including venture capital, sales turnover and profit. The object of research is MSEs that are members of BMT Kalifah Amanah with 95. Type of data collected is of primary data and secondary data. Methods of data analysis used in this research include include linear regression analysis and different T test with the help of SPSS 18. Thus with the financing of BMT Amanah the capital of business, sales turnover and profitability of Micro and Small Enterprises (MSEs) have increased significantly.